Electron microscopic investigation and elemental analysis of titanium dioxide in sun lotion. (10th November 2016) - Sysoltseva, M.; Winterhalter, R.; Wochnik, A. S.; Scheu, C.; Fromme, H.
Abstract: Objective: The objective of this research was to determine the size, shape and aggregation of titanium dioxide (TiO2 ) particles which are used in sun lotion as UV‐blocker. Methods: Overall, six sunscreens from various suppliers and two reference substances were analysed by electron microscopy (EM) techniques in combination with energy dispersive X‐ray spectroscopy (EDS). Because of a high fat content in sun lotion, it was impossible to visualize the TiO2 particles without previous EM sample preparation. Different defatting methods for TiO2 from sun screens were tested. A novel sample preparation method was developed which allowed the characterization of TiO2 particles with the help of EM and EDS. Results: Aggregates of titanium dioxide with the size of primary particles varying between 15 and 40 nm were observed only in five products. In the sun lotion with the highest SPF, only few small aggregates were found. In the sun screen with the lowest SPF, the largest aggregates of TiO2 particles were detected with sizes up to 1.6 μm. In one of the sun lotions, neither TiO2 nor ZnO was found in spite of the labelling. Instead, approx. 500 nm large diamond‐shaped particles were observed. These particles are composed of an organic material as only carbon was detected by EDS. Conclusion: A novel defatting method for sample preparation of titanium dioxide nanoparticles used in sun cosmetics was developed. This method was applied to six different sun lotions with SPF between 30 and 50+. TiO2 particles were found in only five sunscreens. The sizes of the primary particles were below 100 nm and, according to the EU Cosmetic Regulation, have to be listed on the package with the term 'nano'. Abstract : Aggregates of titanium dioxide with the size of primary particles varying between 15 and 40 nm were observed only in five products. In one of the sun lotions, neither TiO2 nor ZnO was found in spite of the labelling. Instead, diamond‐shaped particles app. 500 nm large were observed.